ANALYSIS OF STUDENTS’ ABILITY TO WRITE PROCEDURE TEXTS AT THE INFORMATICS ENGINEERING STUDENTS OF STATE POLYTECHNIC OF CILACAP - Eka Dyah P (Politeknik Negeri Bengkalis, 2017)
Abstract: Mastering writing skill is a better way to communicate. While in practice, some English teachers/lecturers frequently found out that their students’ writings were not well-written due to the students’ lack of writing ability. There are many text genres learnt by the students. One of them is procedure text. The students’ ability to write procedure text is not only measured by their mastery of grammar, but also from its structures and the language features. The data were 23 procedure texts written by the first semester students of Informatics Engineering department at State Polytechnic of Cilacap. This study is acase study in nature by using combination of quantitative and qualitative approaches in analysis. The analysis was done according to communicative purpose, generic structure, and linguistic features of a procedure text. The result of the study showed that all Informatics Engineering students (100%) have achieved the communicative purpose of procedure text, almost all students (97.10%) could implement the generic structures of procedure text in their writings, and some of the students (60.87%) could characterize their procedure texts by using the linguistic features of procedure text.